ANALISIS PENERAPAN MEDIA PEMBELAJARAN BERBASIS KOMPUTER PADA SMK NEGERI 1 KOLAKA MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Husna Saleh; Purnamawati; Anas Arfandi; Alimuddin Sa’ban Miru; Abdul Muis Mappalotteng (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
This study aims to examine the behavior of using e-learning in terms of: (1) the perception of ease of using e-learning (Perceived Ease of Use), (2) the perception of e-learning usefulness (Perceived Usefulness), (3) attitudes in using e-learning (Attitudes toward Using), (4) behavioral intention of using e-learning (Behavioral Intention to Use), and (5) the e learning implementation (Actual Technology Use) in applying computer-based learning media at SMKN 1 Kolaka using the Technology Acceptance Model (TAM) The type of this study is descriptive research. The results of the study indicate that (1) there is a perception of ease of using e-learning (Perceived of Use) in moderate category, (2) there is a perception of e-learning usefulness (Perceived Usefulness) in moderate category, (3) there is an attitude in using e-learning (Attitudes toward Using) with a higher category than other categories, (4) there is a behavioral intention of using e-learning (Behavioral Intention to Use) with a low category compared to the previous level of category, and(5) there is an e-learning implementation (Actual Technology Use) with a low category comparedto the previous level of category.